2019
DOI: 10.31557/apjcp.2019.20.8.2333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Analysis of Linear Discriminant Analysis and Cuckoo-Search Algorithm in the Classification of Breast Cancer from Digital Mammograms

Abstract: Objective:Breast cancer is the most common invasive severity which leads to the second primary cause of death among women. The objective of this paper is to propose a computer-aided approach for the breast cancer classification from the digital mammograms.Methods:Designing an effective classification approach will assist in resolving the difficulties in analyzing digital mammograms. The proposed work utilized the Mammogram Image Analysis Society (MIAS) database for the analysis of breast cancer. Five distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The outcomes revealed that SVM attained good classification accuracy using the features selected by WOA. Chakaravarthy et al 13 designed a system to help physicians analyze digital mammogram images more accurately. Different WTs are employed to extract features from the mammogram images.…”
Section: Related Workmentioning
confidence: 99%
“…The outcomes revealed that SVM attained good classification accuracy using the features selected by WOA. Chakaravarthy et al 13 designed a system to help physicians analyze digital mammogram images more accurately. Different WTs are employed to extract features from the mammogram images.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work, the CuSA and firefly optimization algorithm are modified for the classification of mammogram. 31,32 To the extent of our knowledge, the application of the crow-search optimization (CSO) algorithm for the problem of classification is not reported in the literature. This research paper is one of the first reports of the implementation of nature-inspired original CSO (OCSO) algorithm to address the microcalcification classification in digital mammograms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is very clear that the research related to the usage of optimization algorithms for the task of classification is quite less as in the literature survey. In our previous work, the CuSA and firefly optimization algorithm are modified for the classification of mammogram 31,32 . To the extent of our knowledge, the application of the crow‐search optimization (CSO) algorithm for the problem of classification is not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BRCA) is the most common malignancy in women, with a significantly increasing incidence during the reproductive years [ 1 ]. BRCA is a primary cause of disease and death for women worldwide, [ 2 , 3 ], and most BRCA-related deaths are due to metastasis [ 4 ]. However, because breast cancer is a heterogeneous tumor, there are great differences in histomorphology, immunophenotype, biological behavior, and treatment response.…”
Section: Introductionmentioning
confidence: 99%